Acute Disseminated Encephalomyelitis in an Adult: An Uncommon Case of Paroxysmal Sympathetic Hyperactivity. Issue 7 (24th February 2015) - Holder, Eric K.; McCall, Joseph C.; Feeko, Kristofer J.
Abstract: Acute disseminated encephalomyelitis (ADEM) is an uncommon acute, rapidly progressive autoimmune demyelinating disease of the central nervous system that is most often due to infection or immunization. Generally, it is monophasic, but there is potential for recurrence and risk for development of multiple sclerosis. Although there has been literature documenting autonomic dysreflexia and hypertensive emergency in 2 pediatric cases of ADEM, to our knowledge there has not been a case detailing paroxysmal sympathetic hyperactivity in an adult patient with ADEM. This case report describes a fulminant case of ADEM and serves to expand the list of diagnoses associated with paroxysmal sympathetic hyperactivity.